2019
DOI: 10.1161/jaha.118.010753
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Impact of Recurrent Takotsubo Syndrome: Results From the GEIST Registry

Abstract: Background Current literature only reports variable information from single‐center studies on the recurrence rate, the complications, and the outcome of patients with Takotsubo syndrome ( TTS) experiencing recurrent TTS . Therefore, a detailed description of clinical characteristics, predictors, and the prognostic impact of patients with TTS and recurrences in a multicenter registry is needed. Methods and Results We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 23 publications
4
84
0
6
Order By: Relevance
“…Reported recurrence rates of TTS are variable, ranging from 1% to 11.4% [25][26][27]. Analysis of the multicenter GEIST (German Italian Stress Cardiomyopathy) Registry data failed to identify any independent predictors of TTS recurrence [28]. Presence of malignancy has been shown to be associated with higher risk of TTS in numerous studies [29][30][31], and there are numerous reports of TTS associated with chemotherapy or immunotherapy [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Reported recurrence rates of TTS are variable, ranging from 1% to 11.4% [25][26][27]. Analysis of the multicenter GEIST (German Italian Stress Cardiomyopathy) Registry data failed to identify any independent predictors of TTS recurrence [28]. Presence of malignancy has been shown to be associated with higher risk of TTS in numerous studies [29][30][31], and there are numerous reports of TTS associated with chemotherapy or immunotherapy [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Die Operation 4 Wochen nach Erholung des Myokards erneut anzugehen, erscheint aufgrund des allgemein geringen Rezidivrisikos von < 5 % vertretbar [15]. Allerdings sind Studien erforderlich, die dezidiert das Rezidivrisiko bei Narkose und Operationen untersuchen.…”
Section: Diskussionunclassified
“…New electrocardiographic abnormalities, such as ST-segment elevation or elevation in cardiac troponin are observed. Reported recurrence rates range from 0 to 15% [4][5][6][7][8]. Although a few papers reported that the earliest time of recurrence was 8 days [4,6], in most cases, a relapse occurs within a few months or years [1,4,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%